Molecular characterization and interactome analysis of Trypanosoma cruzi Tryparedoxin 1 - Piñeyro, María Dolores (2011)
Trypanosoma cruzi tryparedoxin 1 (TcTXN1) is an oxidoreductase belonging to the thioredoxin superfamily, which mediates electron transfer between trypanothione and peroxiredoxins. In trypanosomes TXNs, and not thioredoxins, constitute the oxido-reductases of peroxiredoxins. Since, to date, there is no information concerning TcTXN1 substrates in T. cruzi, the aim of this work was to characterize TcTXN1 in two aspects: expression throughout T. cruzi life cycle and subcellular localization; and the study of TcTXN1 interacting-proteins. We demonstrate that TcTXN1 is a cytosolic and constitutively expressed protein in T. cruzi. In order to start to unravel the redox interactome of T. cruzi we designed an active site mutant protein lacking the resolving cysteine, and validated the complex formation in vitro between the mutated TcTXN1 and a known partner, the cytosolic peroxiredoxin. Through the expression of this mutant protein in parasites with an additional 6xHis-tag, heterodisulfide complexes were isolated by affinity chromatography and identified by 2-DE/MS. This allowed us to identify fifteen TcTXN1 proteins which are involved in two main processes: oxidative metabolism and protein synthesis and degradation. Our approach led us to the discovery of several putatively TcTXN1-interacting proteins thereby contributing to our understanding of the redox interactome of T. cruzi.